Palliative Care Implementation in the Intensive Care Unit - Zamharira, Zamharira; Trisyani, Yanny; Emaliyawati, Etika Emaliyawati (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Introduction, Palliative care is a treatment approach whose goal is to improve and optimize the quality of life of patients with serious, incurable illnesses, including ICU patients. The purpose of this study is to see an overview of the implementation of palliative care in the Intensive Care Unit (ICU).Method. This literature review was conducted by using PRISMA guidance, a literature survey through electronic databases namely CINAHL, Science Direct and Pubmed using the keywords ‘palliative care’, ‘intensive care unit’, and; ‘critical care’.Result, there were 6628 articles have been identified, there were 4070 duplicates. There were 2,508 articles that were not related to the title. A total of 50 article titles were available to be analyzed worthly and 10 articles were found that matched the criteria, full text, using Indonesian and English, and publications in the range of year in 2013-2023 period.Conclusion, Palliative care in the ICU has received support from major intensive care organizations such as the American Association of Critical Care Nurses (2017). Despite much support, the quality of palliative care in the ICU has shown little or almost no improvement over time (Ganz & Sapir, 2019). Until now there has been no research that describes the overall implementation of palliative care in the ICU, including in Indonesia. There are still found the obstacles in the implementation of palliative care in the ICU that have not been resolved, so, further research is expected on the implementation of palliative care in the ICU, especially in Indonesia.